2016
DOI: 10.1002/rcm.7609
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase complexes formed between amidoxime ligands and vanadium or iron investigated using electrospray ionization mass spectrometry

Abstract: This study presents a first look at the gas-phase vanadium(V)- and iron(III)-DHIP and -DHPD complexes using electrospray ionization mass spectrometry. These metals form stronger complexes with amidoxime ligands than uranyl(VI), and will affect uranyl(VI) adsorption to amidoxime-based sorbents. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…AOs have two p K a values, (i) p K a1 ≈ 6 and (ii) p K a2 ≈ 13, which correspond to the protonated oxime nitrogen and oxime hydroxy group, respectively. , Thus, at physiological pH, the AO group exists in its neutral form bearing an oxime and amino group. Studies on AO-containing small molecules have revealed these to act as bidentate ligands in organic solvents. , To determine the complexation potential of the present systems in an aqueous environment, qualitative tests with different ratios of Fe­(III) to AO were performed. To allow for an efficient Fe­(III) complexation, metal-to-ligand ratios below 0.5:1 were studied under the assumption that two AO moieties will complex one Fe­(III) ion .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AOs have two p K a values, (i) p K a1 ≈ 6 and (ii) p K a2 ≈ 13, which correspond to the protonated oxime nitrogen and oxime hydroxy group, respectively. , Thus, at physiological pH, the AO group exists in its neutral form bearing an oxime and amino group. Studies on AO-containing small molecules have revealed these to act as bidentate ligands in organic solvents. , To determine the complexation potential of the present systems in an aqueous environment, qualitative tests with different ratios of Fe­(III) to AO were performed. To allow for an efficient Fe­(III) complexation, metal-to-ligand ratios below 0.5:1 were studied under the assumption that two AO moieties will complex one Fe­(III) ion .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on AO-containing small molecules have revealed these to act as bidentate ligands in organic solvents. 65,66 To determine the complexation potential of the present systems in an aqueous environment, qualitative tests with different ratios of Fe(III) to AO were performed. To allow for an efficient Fe(III) complexation, metal-to-ligand ratios below 0.5:1 were studied under the assumption that two AO moieties will complex one Fe(III) ion.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…outside the influence of solvent or other condensed phase effects) in a species‐specific fashion . Since then, ESI has been used to create gas‐phase uranyl species for a range of tandem mass spectrometry (MS/MS), anion photoelectron spectroscopy, and ion mobility studies . ESI and MS/MS have also been used to study and compare the intrinsic dissociation and ion‐molecule reactions of transuranic species …”
Section: Introductionmentioning
confidence: 99%